A novel strategy for a building-integrated diurnal photovoltaic and all-day radiative cooling system. (15th September 2019) - Zhao, Bin; Hu, Mingke; Ao, Xianze; Chen, Nuo; Xuan, Qingdong; Su, Yuehong; Pei, Gang
Abstract: For rooftop building-integrated photovoltaic (BIPV) technology, photovoltaic (PV) modules are typically mounted on the sunny side of a rooftop to receive a high amount of solar irradiance, whereas the opposite side of the rooftop will have free space. This study proposed a novel strategy for building-integrated PV and radiative cooling (RC) system, namely BIPV−RC system, by covering the sunny side of a rooftop with PV modules and its free side with all-day RC modules to integrate solar energy collection and RC utilization into a single building unit. A mathematical model was developed for the proposed BIPV−RC system and a case study was conducted in two tropical cities (Karachi, Pakistan and Riyadh, Saudi Arabia). Results show the total electricity and cooling output of the BIPV−RC system in Riyadh is 462.1 kWh·m −2 and 1315.3 MJ m −2, respectively, approximately 20.7% and 94.0% higher than those in Karachi. Moreover, a comparative study between the BIPV−RC system and the common BIPV and building-integrated RC (BIRC) system was performed and results indicate that the annual total energy output of the BIPV−RC system is nearly 79.1% and 16.8% higher than that of BIPV and BIRC system, respectively. Highlights: A novel strategy for BIPV and all-day radiative cooling hybrid system was proposed. A simulation model of the hybrid system was established and validated. The feasibility of the proposed strategy was numerically demonstrated. The radiative cooling mechanism is more suitable for dry regions.